PotDataset - Alzoubi, Alaa (Cranfield University, 2018)
Pothole Image Dataset: We have developed a new image dataset (PotDataset) for pothole recognition task. The dataset includes images of pothole objects and non-pothole objects. The images were manually annotated, and used to evaluate our recognition method.
Keywords: 'Pothole Images'; 'Pothole Recognition'; 'Deep Convolutional Neural Networks'; 'Artificial Intelligence and Image Processing'; 'Computer Vision'; 'Image Processing'